A Statistical Analysis to Assess the Impact of India’s Export Potential in Petroleum Products and Real Effective Exchange Rate on GCC Countries - Noor, Haris; Raza, Ahmad; Khan, Md Imran; Alomair, Abdulrahman; Azhar, Muhammad (International Journal of Economics and Financial Issues, 2025)
This study explores how the economic growth of the gulf cooperation council (GCC) countries is affected by India’s petroleum product exports and the real effective exchange rate (REER). Annual time series data from 1995 to 2025 are used for empirical support, and the panel autoregressive distributed lag model is used with gross domestic product (GDP) as a dependent variable, serving as a proxy for the economic growth of the GCC. For explanatory variables, the highest exported petroleum product from India to GCC countries and India’s real effective exchange rate are used to determine the short and long-run relationship with the GDP of GCC countries. The findings reveal that petroleum product exports to the GCC countries and the real effective exchange rate significantly impact the GCC countries’ GDP in both the short and long run. Lastly, the Breusch-Pagan test provides evidence of no heteroscedasticity issues, and the Pesaran LM test shows no cross-sectional dependence. In addition, the RESET test confirms the overall model stability in the regression analysis without any misspecification or errors. Unidirectional causality is confirmed through the Granger test, where petroleum product exports and the real effective exchange rate affect the GDP of the GCC countries.